ANALISA STRATEGI PENINGKATAN SERTIFIKASI HALAL SEKTOR KULINER DI BANGKA SELATAN - Sifa Aprilia; Anita Priantina (International Journal Mathla’ul Anwar of Halal Issues, 2022)
This study discusses priority problems, priority solutions, and priority strategies in increasing the number of halal certifications in the culinary sector in South Bangka Regency. The research method uses the Analytical Network Process (ANP). Based on the research results, the priority problem faced by South Bangka MSME actors is the lack of information dissemination and socialization related to halal certification. The priority solution that can be offered in increasing the number of halal certifications in South Bangka is to hold training related to halal certification, starting from filing to issuing halal certification. And the priority strategy implemented in increasing the number of halal certifications in South Bangka is to increase information, education, and socialization related to halal certification to business actors.